Pendampingan Pengolahan Ikan Tawes Menjadi Makanan Olahan untuk Penderita TBC Anak - Dartini; Fadli Felayani; Nabilla Pramitya; Prima Selvia Megawati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2026)
Tuberculosis (TBC) remains a significant public health issue, particularly among children, with a high incidence rate in several areas of Banyumas Regency. In 2022, a total of 66 pediatric TB cases were reported, representing the highest number in the region. One of the major risk factors contributing to the severity of tuberculosis in children is poor nutritional status. Although tawes fish is abundantly available as a local food resource, its utilization as a nutritious dietary option for children remains limited and relatively unappealing. This community service program aimed to enhance community knowledge and skills in processing tawes fish into nutritious food products to support the improvement of nutritional status among children with tuberculosis. The program was conducted on August 24, 2025, involving 25 members of the Family Welfare Empowerment (PKK) cadres. The methods employed included nutrition education, health promotion, and hands-on assistance in the preparation of tawes fish nuggets. Evaluation results demonstrated an improvement in participants’ nutritional knowledge, with an average post-test score increase of 23.9% compared to the pre-test. This program was considered effective in strengthening community capacity to utilize local food resources as alternative nutritious foods to support the prevention and management of childhood tuberculosis.